Contradiction or coordination? The spatiotemporal relationship between landscape ecological risks and urbanization from coupling perspectives in China. (20th August 2022) - Shi, Yu; Feng, Chen-Chieh; Yu, Qianru; Han, Rui; Guo, Luo
Abstract: Rapid urbanization in developing countries has been shown to have higher intensities of development and more frequent human-ecosystem interactions. Urbanization in China is highly representative of such development, and given its magnitude, poses severe risks if not irreversible consequences to the sustainability of natural ecosystem. The UN Sustainable Development Goals (SDGs) has highlighted the necessity for humanity to live in harmony with ecosystems for achieving a sustainable state. Evaluating the coupling states between urbanization and ecological risks and identifying the distribution of coordinated and unbalanced types are two crucial steps for ensuring sustainability. To date, nonetheless, there is a scarcity of macro and overall assessment of ecological risk for the whole China at a finer resolution. This study combined landscape pattern indices to better reveal the state of landscape ecological risk (LER) at a grid scale of 10km × 10km in 1990–2015 for entire China. Considering the geographical differences, this study further evaluated how the urbanization factors of population density (PD), GDP density (GDPD), build-up land proportion (BLP), comprehensive urbanization level (CUL) led to major LER changes in different regions, using a geographical detector model (GDM). Finally, the coupling coordination degree (CCD) between LER and its dominated urbanization factors of different regions was investigated. The results show that the urbanization intensified the LER, and risk hot-spots were mostly distributed in the southeast of China dominated with high levels of urbanization. In addition, LER hot-spots were more concentrated in aquatic, cultivated land and build-up land. The major urbanization factors affecting China's LER included PD, BLP and CUL. More important, the CCD level between three urbanization factors and LER improved with time, but most parts of China remained in an unbalanced development state. Through the identified regional differences of coupling coordination types, the degree of contradiction between local urbanization and LER can be known, so as to harmonize the environment and humanity. Graphical abstract: Image 1